SYMBOLIC MEANINGS AND THE STRUCTURE OF DEATH RITUALS DISCOURSE IN RURAL JAVANESE SOCIETY: AN ETHNOGRAPHIC STUDY IN MEJING VILLAGE, MAGELANG REGENCY - Puji Laksono (CV. Lafadz Jaya, 2026)
The death ritual is one of the ritual which is important in the life of Javanese community. One of community that still holds the ritual is Mejing village’ community. The purpose of this study is to analyze the symbolic meaning, and structure in the death rituals of the Mejing Village community in Magelang Regency, which is part of Javanese culture. There, the community understands death rituals not only as a form of respect for the deceased but also a cultural practice that reflects the community's belief system, social values, and social relations. The research method is a qualitative ethnographic approach. Data were collected through in-depth interviews, participant observation, and documentation. The results indicate that the death rituals in Mejing Village have structured stages and are rich in symbolic meaning, including tahlilan, kenduri, and cultural practices that reflect the values of social solidarity and respect for ancestors. This research provides an academic contribution to the study of cultural anthropology and efforts to preserve local traditions amid social change.